2021
DOI: 10.1002/jaba.897
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of social interaction on the results of preference assessments for leisure items

Abstract: A variable that may influence the outcomes of stimulus preference assessments (SPAs) is whether social interaction is provided during the stimulus access period. In Experiment 1, we compared the outcomes of a Solitary paired stimulus preference assessment (PSPA) (toys only), Social PSPA (toys plus social interaction), and Combined PSPA (toys alone and toys plus social interaction) to determine whether the addition of social interaction influenced preference for toys in preschool children. In Experiment 2, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…However, the benefits of systematic, within‐session manipulations of the availability of social interaction could be retained by including approach (i.e., therapist moves away from participant) and avoidance (i.e., therapist moves toward participant) test trials based on the different conditions or phases evaluated in previous research (Call et al, 2013; Morris & Vollmer, 2020). Such a procedure may also serve to bridge the gap between more naturalistic, time‐allocation‐based assessments of sociability and more individualized, structured, selection‐based assessments of preference for social versus solitary play with different leisure stimuli (Goldberg et al, 2017; Kanaman et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, the benefits of systematic, within‐session manipulations of the availability of social interaction could be retained by including approach (i.e., therapist moves away from participant) and avoidance (i.e., therapist moves toward participant) test trials based on the different conditions or phases evaluated in previous research (Call et al, 2013; Morris & Vollmer, 2020). Such a procedure may also serve to bridge the gap between more naturalistic, time‐allocation‐based assessments of sociability and more individualized, structured, selection‐based assessments of preference for social versus solitary play with different leisure stimuli (Goldberg et al, 2017; Kanaman et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A disproportional preference for one type of stimulus (e.g., edible items) over other types of stimuli has been referred to as preference displacement in past studies (DeLeon et al, 1997). Previous studies have investigated preference displacement of different stimulus classes by first conducting single-class preference assessments and then combining the most preferred stimuli from each single-class assessment into a combined-class preference assessment (e.g., leisure vs. edible) (Andakyan et al, 2016;Bojak & Carr, 1999;Carter & Zonneveld, 2020;Clark et al, 2020;Conine & Vollmer, 2019;DeLeon et al, 1997;Fahmie et al, 2015;Hoffman et al, 2017;Kanaman et al, 2022;Lucock et al, 2020;Ortega et al, 2012;Sipila-Thomas et al, 2021;Slanzi et al, 2020). Some studies evaluating preference displacement found that participants disproportionately selected edible items over leisure items when presented in the same preference assessments (Bojak & Carr, 1999;DeLeon et al, 1997;Fahmie et al, 2015).…”
Section: Evaluating Patterns Of Preference Displacement Including Soc...mentioning
confidence: 99%
“…Other variables, such as social interactions, can also be evaluated in stimulus preference assessments. Kanaman et al (2022), for example, evaluated the effects of social interaction on the results of preference assessments for leisure items among typically developing children. In this study, preference assessments were conducted with toys alone and toys with social interaction.…”
Section: Evaluating Patterns Of Preference Displacement Including Soc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Both raters reviewed and discussed the disagreements and ultimately reached a consensus about whether they met inclusion criteria. Disagreements primarily pertained to studies that evaluated social interaction in general (e.g., Kanaman et al, 2022) but did not evaluate different types of social stimuli. All data were coded from the Method and Results sections of each study by the second author.…”
Section: Interrater Agreementmentioning
confidence: 99%